Additive-treated corn silages for growing cattle - Bolsen, K.; Ilg, H.; Kirch, B.; Laytimi, A.; Lomas, Lyle W. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Whole-plant corn silages were treated with USO3M or Silo-Best Soluble® in one trial and with Garst M-74® in a second trial. In Trial 1 all three silages were well preserved and moderately stable in the air. USO3M silage lost less dry matter during fermentation than control or Silo-Best silages. Cattle fed the USO3M silage made 7.6% faster gains and were 5.2% more efficient than those fed the control silage. Cattle performance with the Silo-Best Soluble and control silages was similar. In trial 2, heifer gains were nearly identical for both control and Garst M-74 silages.
Keywords: Beef; Corn silage; Fermentation; Performance